Integration of coal pyrolysis process with iron ore reduction： Reduction behaviors of iron ore with benzene-containing coal pyrolysis gas as a reducing agent - Li, Xin; Hui, Helong; Li, Songgeng; He, Lu; Cui, Lijie (Chinese journal of chemical engineering, 2016)
An integrated coal pyrolysis process with iron ore reduction is proposed in this article. As the first step, iron oxide reduction is studied in a fixed bed reactor using simulated coal pyrolysis gas with benzene as a model tar com- pound. Variables such as reduction temperature, reduction time and benzene concentration are studied. The car- bon deposition of benzene results in the retarded iron reduction at low temperatures. At high temperatures over 800 ~C, the presence of benzene in the gas can promote iron reduction. The metallization can reach up to 99% in 20 min at 900 ~C in the presence of benzene. Significant increases of hydrogen and CO/CO2 ratio are observed in the gas. It is indicated that iron reduction is accompanied by the reforming and decomposition of benzene. The degree of metallization and reduction increases with the increasing benzene concentration. Iron oxide can nearly completely be converted into cementite with benzene present in the gas under the experimental conditions. No sintering is found in the reduced sample with benzene in the gas.